Late Quaternary vegetation and lake system dynamics in north-eastern Siberia: Implications for seasonal climate variability - Biskaborn, Boris (Prof.); Subetto, D. A.; Savelieva, L. A.; Vakhrameeva, P. S.; Hansche, A.; Herzschuh, Ulrike (Prof. Dr.); Klemm, J.; Heinecke, L.; Pestryakova, Luidmila A. (Prof. Dr.); Meyer, H.; Kuhn, G.; Diekmann, Bernhard (PD Dr. habil.) (Quaternary Science Reviews, 2016)
Although the climate development over the Holocene in the Northern Hemisphere is well known, palaeolimnological climate reconstructions reveal spatiotemporal variability in northern Eurasia. Here we present a multi-proxy study from north-eastern Siberia combining sediment geochemistry, and diatom and pollen data from lake-sediment cores covering the last 38,000 cal. years. Our results show major changes in pyrite content and fragilarioid diatom species distributions, indicating prolonged seasonal lake-ice cover between similar to 13,500 and similar to 8900 cal. years BP and possibly during the 8200 cal. years BP cold event. A pollen-based climate reconstruction generated a mean July temperature of 17.8 degrees C during the Holocene Thermal Maximum (HTM) between similar to 8900 and similar to 4500 cal. years BP. Naviculoid diatoms appear in the late Holocene indicating a shortening of the seasonal ice cover that continues today. Our results reveal a strong correlation between the applied terrestrial and aquatic indicators and natural seasonal climate dynamics in the Holocene. Planktonic diatoms show a strong response to changes in the lake ecosystem due to recent climate warming in the Anthropocene. We assess other palaeolimnological studies to infer the spatiotemporal pattern of the HTM and affirm that the timing of its onset, a difference of up to 3000 years from north to south, can be well explained by climatic teleconnections. The westerlies brought cold air to this part of Siberia until the Laurentide ice sheet vanished 7000 years ago. The apparent delayed ending of the HTM in the central Siberian record can be ascribed to the exceedance of ecological thresholds trailing behind increases in winter temperatures and decreases in contrast in insolation between seasons during the mid to late Holocene as well as lacking differentiation between summer and winter trends in paleolimnological reconstructions. (C) 2015 Elsevier Ltd. All rights reserved.